A molecular timescale for eukaryote evolution with implications for the origin of red algal-derived plastids - Jürgen F. H. Strassert (Nature Portfolio, 2021)
There are several competing hypotheses for the acquisition of red algal-derived plastids by eukaryotic phytoplankton. Here, the authors use Bayesian molecular clock analyses to evaluate the chronological possibility of the proposed plastid origins and transmissions.